Fiscal policy, institutions and economic growth in Asian economies: evidence from the Pedroni's cointegration approach - Abdullah, Hussin; Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi (Canadian Center of Science and Education, 2008)
This paper investigates the relationship between fiscal policy, institutions and economic growth in Asian between 1982 and 2001 through the application of Pedroni’s Cointegration approach. It examines three different channels through which fiscal policy can affect long run economic growth in Asia. The first channel is when components of fiscal policy affects the real per capita GDP and the second channel is when the institutions included in components of fiscal policy affects the real per capita GDP. The third channel is when institutions interact with aggregate of government expenditure and aggregate of fiscal policy affects the real per capita GDP. The Pedroni Cointegration result establishes a long run relationship between fiscal policy, institutions and economic growth. We find positive and statistically significant impact of health and education expenditure, aggregate of government expenditure, aggregate of fiscal policy and institutions on real per capita GDP. We also find that the defence expenditure, distortionary taxation and budget balance are significantly and negatively related to real per capita GDP. Furthermore, we find that aggregate of government expenditure and aggregate of fiscal policy variables interact with institutions variable and have a potential impact on long-run steady-state levels of growth.